The pectoral muscles of bony fishes and tetrapods: a new insight - Diogo, Rui (2007)
The Osteichthyes, including bony fishes and tetrapods, is a highly speciose group of vertebrates, comprising more than 42,000 living species. The anatomy of osteichthyans has been the subject of numerous comparative studies, but most of these studies concern osteological structures; much less attention has been paid to muscles. The most detailed comparative analyses of osteichthyan pectoral muscles that were actually based on a direct observation of representatives of various major actinopterygian and sarcopterygian groups were provided several decades ago by authors such as Howell and Romer. Despite the quality of their work, these authors did not have access to much information that is now available. In the present work, an updated discussion on the homologies and evolution of the osteichthyan pectoral muscles is provided, based on the authors´ own analyses and on a survey of the literature, both old and recent. It is stressed that much caution should be taken when the results obtained in molecular and developmental studies concerning the pectoral muscles of model actinopterygians such as the teleostean zebrafish are discussed and compared with the results obtained in studies concerning model sarcopterygians from clades such as the Amphibia and/or the Amniota. This is because, as shown here, as a result of the different evolutionary routes followed within the actinopterygian and the sarcopterygian clades none of the individual muscles found, for example, in derived actinopterygians such as teleosts is found in derived sarcopterygians such as tetrapods. It is hoped that the information provided in the present work may help in paving the way for future analyses of the pectoral muscles in taxa from different osteichthyan groups and for a proper comparison between these muscles in those taxa